An Analysis of the Use of Artificial Intelligence and Its Impact on the Originality of Academic Assignments among Educational Technology Students in the Faculty of Education - Reski Riana Sultan; Abdul Hakim; Nur Wahyuningsih Ibrahim (The Future of Education Journal, 2026)
This study aims to analyze the forms of Artificial Intelligence (AI) utilization by students, the level of originality of academic assignments produced with AI assistance, the positive and negative impacts of AI use, and the efforts students make to maintain the originality of their academic work. A descriptive qualitative approach was used, with data collected through observation, semi-structured interviews, documentation, and a questionnaire (Google Form) distributed to 15 sixth-semester students of the Educational Technology Study Program at Universitas Negeri Makassar and 2 lecturers. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data reduction, data display, and conclusion drawing. The results show that ChatGPT and Gemini are the AI applications most frequently used by students, mainly to search for references, obtain initial information, and improve text structure at the early stage of assignment writing. The positive impacts of AI use include time efficiency, ease of generating initial ideas, and improved writing quality, while the negative impacts include the risk of technological plagiarism and potential dependency that may reduce students’ critical thinking when AI is used excessively. The originality of students’ academic work is generally still well maintained through concrete efforts such as reading and comprehending information before use, paraphrasing in their own words, comparing AI-generated information with valid books or scientific journals, and checking text similarity using Turnitin. Lecturers emphasized that AI should be positioned as a learning partner or supporting tool rather than a substitute for students’ independent thinking process.